2022
DOI: 10.3389/fped.2021.809536
|View full text |Cite
|
Sign up to set email alerts
|

Cost Efficacy of Rapid Whole Genome Sequencing in the Pediatric Intensive Care Unit

Abstract: The diagnostic and clinical utility of rapid whole genome sequencing (rWGS) for critically ill children in the intensive care unit (ICU) has been substantiated by multiple studies, but comprehensive cost-effectiveness evaluation of rWGS in the ICU outside of the neonatal age group is lacking. In this study, we examined cost data retrospectively for a cohort of 38 children in a regional pediatric ICU (PICU) who received rWGS. We identified seven of 17 patients who received molecular diagnoses by rWGS and had re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…The early use of genomic sequencing strategies in the critically unwell neonate has shown promise in a number of studies [ 13 , 14 ]. While there have been impressive diagnostic yields demonstrated in studies to date, cost-effectiveness has only been demonstrated in a PICU and not a NICU population [ 15 ]. Ongoing trials as part of the Newborn Sequencing in Genomic Medicine and Public Health (NSIGHT) consortium are being performed to establish the benefits of genomic sequencing in newborns as well as the cost effectiveness of such a strategy [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The early use of genomic sequencing strategies in the critically unwell neonate has shown promise in a number of studies [ 13 , 14 ]. While there have been impressive diagnostic yields demonstrated in studies to date, cost-effectiveness has only been demonstrated in a PICU and not a NICU population [ 15 ]. Ongoing trials as part of the Newborn Sequencing in Genomic Medicine and Public Health (NSIGHT) consortium are being performed to establish the benefits of genomic sequencing in newborns as well as the cost effectiveness of such a strategy [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to binary outcomes like mortality, a handful of studies have attempted to quantify the effects of genomic sequencing on patient quality‐adjusted life years (QALYs) (Farnaes et al, 2018; Sanford Kobayashi et al, 2022; Schofield et al, 2019). The QALY is generally preferred over other outcome measures because it combines both the longevity and quality of life attributable to the studied intervention into a one number that can be used for comparison between studies (Weinstein et al, 2009).…”
Section: Data Evaluating Implementation Of Genomic Testingmentioning
confidence: 99%
“…The QALY is generally preferred over other outcome measures because it combines both the longevity and quality of life attributable to the studied intervention into a one number that can be used for comparison between studies (Weinstein et al, 2009). In one cost utility analysis of a PICU cohort that underwent rWGS, a total of 12.1 QALYs were gained from seven patients modeled (Sanford Kobayashi et al, 2022). In Australia, a cohort of 80 infants who received exome sequencing was determined to have gained 36 QALYs as a result when cascade testing and parent reproductive outcomes were included in the analysis (Schofield et al, 2019).…”
Section: Data Evaluating Implementation Of Genomic Testingmentioning
confidence: 99%
See 2 more Smart Citations